Implementing Reverse Phase Protein Array Profiling as a Sensitive Method for the Early Pre‐Clinical Detection of Off‐Target Toxicities Associated with Sunitinib Malate. Issue 4 (19th March 2019) - O'Farrell, Alice C.; Miller, Ian S.; Evans, Rhys; Alamanou, Marina; Cary, Maurice; Mallya Udupi, Girish; Lafferty, Adam; Monsefi, Naser; Cremona, Mattia; Prehn, Jochen H. M.; Verheul, Henk M.; Gallagher, William M.; et al.
Abstract : Purpose: The tyrosine kinase inhibitor (TKI) sunitinib is a multi‐targeted agent approved across multiple cancer indications. Nevertheless, since approval, data has emerged to describe a worrisome side effect profile including hypertension, hand‐foot syndrome, fatigue, diarrhea, mucositis, proteinuria, and (rarely) congestive heart failure. It has been hypothesized that the observed multi‐parameter toxicity profile is related to "on‐target" kinase inhibition in "off‐target" tissues. Experimental Design: To interrogate off‐target effects in pre‐clinical studies, a reverse phase protein array (RPPA) approach is employed. Mice are treated with sunitinib (40 mg kg −1 ) for 4 weeks, following which critical organs are removed. The Zeptosens RPPA platform is employed for protein expression analysis. Results: Differentially expressed proteins associated with damage and/or stress are found in the majority of organs from treated animals. Proteins differentially expressed in the heart are associated with myocardial hypertrophy, ischaemia/reperfusion, and hypoxia. However, hypertrophy is not evidenced on histology. Mild proteinuria is observed; however, no changes in renal glomerular structure are visible via electron microscopy. In skin, proteins associated with cutaneous inflammation, keratinocyte hyper‐proliferation, and increased inflammatory response are differentially expressed. Conclusions and Clinical Relevance: It is posited that pre‐clinical implementation of a combined histopathological/RPPA approach provides a sensitive method to mechanistically elucidate the early manifestation of TKI on‐target/organ off‐target toxicities.